Orthodontic movement of a maxillary central incisor with a horizontal root fracture treated using an intra-radicular fibre splint - Aditi Kapur; A Utreja; A Goyal; P Pankaj (Wolters Kluwer Medknow Publications, 2013)
This paper reports the case of a 15-year-old boy with a horizontal root fracture in the left maxillary central incisor along with class II division 1 malocclusion for whom a fixed orthodontic treatment was planned. The fracture was present at the junction of apical and middle-third as a result of trauma 2 years back. No splinting was carried out at that time and the tooth was found to be vital, asymptomatic and showed a type-1 repair pattern. An intentional root canal treatment was carried out for placement of an intra-radicular fiber splint, nearly 3 mm beyond the fracture line. Orthodontic treatment was initiated after a month; to which the fractured and splinted tooth responded successfully. This report highlights the successful use of an intra-radicular splint for horizontally fractured tooth requiring orthodontic treatment.